The inverse `f^-1(x)` of a function f(x) can be found in the following way.

Usually the graph of a function f(x) is written as y = f(x). All points on the graph represent (x, f(x)).

Take y = f(x) and rewrite it in a form where y is the independent variable and x is the dependent variable. It is possible to find the inverse of a function only where one value of f(x) does not correspond to more than one value of x.

For example, consider the function f(x) = 3x + 5

y = 3x + 5

Now express x as an expression with y

=> 3x = y - 5

=> x = (y - 5)/3

Therefore the inverse of f(x) is `f^-1(x) = (x - 5)/3`

In a similar manner the inverse of any function can be found if there is a one-to-one correspondence between x and f(x).

## See eNotes Ad-Free

Start your **48-hour free trial** to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Already a member? Log in here.